Fostering Innovative Cultures in Sport Leadership, Innovation and Change - Skinner, James (Springer International Publishing, 2018)
Analysing the trends that are emerging in sport enterprises such as advancements in technology and social media, the authors of this illuminating book tackle the issue of how to create new opportunities in such a changing industry. Providing valuable reading for sports business scholars, this book draws on examples from inventive companies as well as inspirational sports leaders and illustrates the various drivers behind innovation. Addressing the need for a culture of innovation within sports enterprises, the authors reveal sustainable ways for companies to stay ahead of the game in an increasingly competitive global sport market.